Comments on the Extraperitoneal Approach for Standard Laparoscopic Radical Prostatectomy: What Is Gained and What Is Lost. (8th August 2011) - Liatsikos, Evangelos; Kyriazis, Iason; Kallidonis, Panagiotis; Do, Minh; Haefner, Tim; Dietel, Anja; Holze, Sigrun; Ragavan, Narasimhan; Stolzenburg, Jens-Uwe
Abstract : Laparoscopic extraperitoneal radical prostatectomy (LERP) is considered the standard care treatment option for the management of localized and locally advanced prostatic cancer (PCa) in many institutes worldwide. In this work, the main advantages and disadvantages of LERP approach are reviewed with regard to its outcomes, the complication management, the learning curve, and the extend of pelvic lymph node dissection (PLND). It is concluded that LERP demonstrates comparable cancer control, urinary continence, and potency outcomes with the open and the robot-assisted radical prostatectomy, while offering advantages in complication management in comparison to the transperitoneal approach. Learning curve of LERP is considered long and stiff and significantly affects perioperative outcomes and morbidity, cancer control, and functional results. Thus, close mentoring especially in the beginning of the learning curve is advised. Finally, LERP still has a role in the limited or modified PLND offered in intermediate risk PCa patients.